2019
DOI: 10.1016/j.apergo.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Enactments and the design of trail running equipment: An example of carrying systems

Abstract: Sports equipment brands have increasingly turned to experience-centered design, meaning the integration of users' activity into the design process. From an enactive perspective, this research investigated two entries of collecting and analyzing interactions between trail runners and their equipment. The paper articulates two studies. Study 1 analyzed traces of enactments on online forums and showed that trail runners reported the issues they enacted while running and reflexively posted the traces of their acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
0
11
0
3
Order By: Relevance
“…With regard to this point, it has been shown that participants in team sports can collaboratively modify their offensive and defensive strategies to co-adapt to changing environmental constraints (e.g., the opposite team) (see Duarte et al, 2012). Such adaptability has been described in music and sport at both behavioral and phenomenological 2 levels (e.g., Schiavio and Høffding, 2015; Hauw, 2018; Rochat et al, in press), with demonstrations of how self and other, behavior and experience, are in fact intrinsically interdependent at various levels and timescales. Jacobs and Michaels (2006), in a similar vein, considered expert performance as a dynamical system comprising performer, tools, the environment, and other individuals.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to this point, it has been shown that participants in team sports can collaboratively modify their offensive and defensive strategies to co-adapt to changing environmental constraints (e.g., the opposite team) (see Duarte et al, 2012). Such adaptability has been described in music and sport at both behavioral and phenomenological 2 levels (e.g., Schiavio and Høffding, 2015; Hauw, 2018; Rochat et al, in press), with demonstrations of how self and other, behavior and experience, are in fact intrinsically interdependent at various levels and timescales. Jacobs and Michaels (2006), in a similar vein, considered expert performance as a dynamical system comprising performer, tools, the environment, and other individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Dans le domaine des sciences du sport et de l'intervention en milieu sportif, les recherches ont notamment porté sur l'activité des sportifs de haut-niveau en compétition (prise de décision, connaissances construites et mobilisées, dynamique émotionnelle) (Rochat, Gesbert, Seifert & Hauw, 2018 ;Sève, Ria, Poizat, Saury, & Durand, 2007 ;Sève, Saury, Theureau & Durand, 2002) ; sur l'activité des entraîneurs et la relation entraîneur-athlètes (d'Arripe-Longueville, Saury, Fournier, & Durand, 2001), ou encore sur la coopération et la coordination dans les situations sportives (Bourbousson, Poizat, Saury, & Sève, 2011) le tout articulé à la conception d'aides à la performance sportive (Sève, Poizat, Saury, & Durand, 2006). On notera également des recherches sur l'activité des athlètes en lien avec la prise de produits dopants (Hauw & Mohamed, 2015) dans une visée de conception de situations d'accompagnement, ainsi que sur l'activité dans les situations sportives ou d'entraînement instrumentées en lien avec la conception de matériel sportif (Rochat, Hauw, & Seifert, 2019).…”
Section: Extension Et Développement Du Programme « Cours D'action » Dunclassified
“…No campo das ciências do ddesporte e de intervenção em meio ddesportivo, as pesquisas voltaram-se notadamente para a atividade de ddesportistas de alto nível em competição (tomada de decisão, conhecimentos construídos e mobilizados, dinâmica emocional) (Sève, Saury, Theureau & Durand, 2002 ;Sève, Ria, Poizat, Saury & Durand, 2007 ;Rochat, Gesbert, Seifert & Hauw, 2018) ; para a atividade dos treinadores e a relação treinador-atletas (d'Arripe-Longueville, Saury, Fournier & Durand, 2001), ou ainda para a cooperação e a coordenação em situações ddesportivas (Bourbousson, Poizat, Saury & Sève, 2011) o todo articulado com a concepção de ajuda para performance ddesportiva (Sève, Poizat, Saury & Durand, 2006). Notam-se, também, pesquisas sobre a atividade de atletas em relação ao uso de produtos dopantes (Hauw & Mohamed, 2015) com finalidade de concepção de situações de acompanhamento, bem como pesquisas acerca da atividade em situações ddesportivas ou de treino instrumentadas ligadas à concepção de material ddesportivo (Rochat, Hauw & Seifert, 2019).…”
Section: Laboreal Volume 16 Nº2 | 2020unclassified